Memorial dedicated to the frigate Cleopatra - Ghosh, Ayan (2023)
Memorial dedicated to the commander, officer, and sailors of the East India Company's steam frigate Cleopatra that sank in a hurricane off the Malabar coast on 15th April 1847. Constructed at Northfleet, the ship arrived at Mumbai on 19th April 1840 and operated as a transport and mail steamer between Mumbai to Karachi, Aden, and Suez. The memorial was erected by officers and seamen of the Indian Navy.